Analysis Of Leadership, Work Motivation, And Work Environment On Civil Servants' Performance At State Senior High School 2 Binjai - Tarisa Oktafia Devi; Wilchan Robain; Kholilul Kholik (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the influence of leadership, work motivation, and work environment on the performance of civil servants at Sma Negeri 2 Binjai, The research approach that is widely used in this study is quantitative research, This research was conducted at SMA Negeri 2 Binjai located at Jl. Padang No.8, Rambung Dalam, Kec. Binjai Sel, the population in this study were teachers and educators with Civil Servant (PNS) status totaling 63 people, The sampling technique used in this study was saturated sampling where all populations were sampled, the analysis technique used in this study was multiple linear regression analysis, the results of this study are the Leadership variable has a positive and significant effect on the Performance of Civil Servants of SMAN 2 Binjai. The Motivation variable has a positive and significant effect on the Performance of Civil Servants of SMAN 2 Binjai. The Work Environment variable has a positive and significant effect on the Performance of Civil Servants of SMAN 2 Binjai. The independent variables consisting of Leadership ( ) , Motivation ( ) , and Work Environment ( ) , simultaneously have a significant influence on the performance of Civil Servants at SMAN 2 Binjai.